The non-modifiable factors age, gender, and genetics influence resistance exercise - Viecelli, Claudio; Ewald, Collin Y. (Frontiers in Aging, 2022)
Muscle mass and force are key for movement, life quality, and health. It is well established that resistance exercise is a potent anabolic stimulus increasing muscle mass and force. The response of a physiological system to resistance exercise is composed of non-modifiable (i.e., age, gender, genetics) and modifiable factors (i.e., exercise, nutrition, training status, etc.). Both factors are integrated by systemic responses (i.e., molecular signaling, genetic responses, protein metabolism, etc.), consequently resulting in functional and physiological adaptations. Herein, we discuss the influence of non-modifiable factors on resistance exercise: age, gender, and genetics. A solid understanding of the role of non-modifiable factors might help to adjust training regimes towards optimal muscle mass maintenance and health.